2007
DOI: 10.1177/0899764007300407
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Fraud in Nonprofit Organizations: Occurrences and Deterrents

Abstract: Losses due to fraudulent activities are particularly troublesome in the nonprofit sector because they directly reduce resources available to address tax-exempt purposes. The ensuing bad publicity also may reduce contributions and grants in subsequent periods. This article uses data provided by Certified Fraud Examiners to report on the types of fraud they identified in nonprofit organizations and the characteristics of both the victims and the perpetrators of the fraudulent activities. Based on the analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
159
0
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(171 citation statements)
references
References 14 publications
4
159
0
8
Order By: Relevance
“…(Mellahi & Wilkinson, 2004, p. 268) The study of charity misconduct has tended to focus on instances of occupational fraud, of which there are two major types: fraud conducted against the organization (e.g. misappropriation of cash by an employee) and fraud conducted by the organization such as the deliberate misreporting of financial performance (Greenlee, Fischer, Gordon & Keating, 2007). Previous research has focused on the nature of fraud in the US nonprofit sector, the organizations subject to fraud, and perpetrators of said action (Archambeault, Webber & Greenlee, 2015).…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…(Mellahi & Wilkinson, 2004, p. 268) The study of charity misconduct has tended to focus on instances of occupational fraud, of which there are two major types: fraud conducted against the organization (e.g. misappropriation of cash by an employee) and fraud conducted by the organization such as the deliberate misreporting of financial performance (Greenlee, Fischer, Gordon & Keating, 2007). Previous research has focused on the nature of fraud in the US nonprofit sector, the organizations subject to fraud, and perpetrators of said action (Archambeault, Webber & Greenlee, 2015).…”
Section: Literaturementioning
confidence: 99%
“…Empirical research by Greenlee et al (2007) and Holtfreter (2008) (Archambeault et al, 2015). Consequently, much of this exploratory work has focused on nonprofit subsectors such as Human and Health Services (e.g.…”
Section: Literaturementioning
confidence: 99%
“…Petrovits, Shakespeare, and Shih (2011) reported that having a GCO increases the likelihood that an NPO has internal control deficiencies during the post-GCO period. In turn, weak internal control allows fraud to be perpetrated, prevents an NPO from operating efficiently, and thereby weakens the NPO's viability (Greenlee, Fischer, Gordon, & Keating, 2007;Wells, 2005). Overall, while the prior literature suggested several facets to the decision to give a going concern opinion, indicators of fiscal distress play a primary role.…”
Section: Gcos and Nonprofit Organizationsmentioning
confidence: 99%
“…One study of fraud in nonprofit organizations found that almost half of all cases of fraud were detected by tips from within the organization or after an internal audit; almost one-quarter were detected by accident and only 12 percent were found by an external auditor. The study concluded that clear lines of authority, enforcement of proper procedures for authorization of transactions, board engagement, and an audit committee were the most effective organizational controls against fraudulent behavior in nonprofit organizations (Greenlee, Fischer, Gordon, & Keating, 2007 The Budgets are Fake…”
Section: Financial Information and The Grant Application Processmentioning
confidence: 99%